Angina in primary care in Goa, India: sex differences and associated risk factors. Issue 1 (11th July 2010) - Nazareth, Irwin; D'Costa, Gladstone; Kalaitzaki, Eleftheria; Vaidya, Raj; King, Michael
Abstract : Background: Little is known about the prevalence of angina in people seen in Indian general practices. The authors assessed the prevalence of angina and its associated risk factors in Goan general practices. Methods: Cross-sectional study on consecutive attendees in nine private general practices in Goa, India. All participants completed the Rose Angina Questionnaire, to ascertain the presence of angina. Other demographic, clinical and biochemical data were also collected. Results: 1556 (626 men and 930 women) consecutive attendees aged 30 to 75 years. Angina was detected in 37 (5.9%, 95% CI 2.4 to 9.4%) men and 99 (10.6%, 95% CI=7.4 to 11.2%) women. The prevalence of angina increased with age in both sexes but was greater in women between aged 46–60 (OR=4.3 (95% CI 2.0 to 9.2)) when compared with men. When compared with men, the odds of angina in women of all ages was 2.03 (95% CI 1.10 to 3.75) after controlling for confounders. Angina was associated with depressive and/or anxiety symptoms in both sexes (men OR=5.65, 95% CI=2.25 to 14.16; women OR=2.18, 95% CI=1.01 to 4.69) and with hypertension in men (OR=3.82, 95% CI=1.57 to 9.30) and family history of coronary heart disease (OR=1.53, 95% CI 1.05 to 2.24) in women. Borderline/high total cholesterol levels (OR=0.5, 95% CI 0.28 to 0.89) in women were associated with a reduced risk of angina. Conclusion: Women attending general practices in Goa, India are at greater risk of angina than men. Depression/anxiety is strongly associated with angina. Greater awareness of the general practitioners to the disparity in angina between the sexes and its association with psychological distress is required.